COVID-19: Peer Support and Crisis Communication Strategies to Promote Institutional Resilience - Wu, Albert W. (Ann Intern Med, 2020)
Caring for patients with the novel coronavirus infection is placing great stress on health care systems and health care workers. On the basis of their experiences responding to other pandemics, the authors summarize lessons learned and offer some best practices for facilitating organizational resilience and supporting health care workers during the COVID-19 pandemic.